2014
DOI: 10.26524/14112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Repeated Sprint Ability and Fatigue Index among Male Handball Players With Respect To Different Playing

Abstract: The intent of the present study was to compare repeated sprint ability and fatigue index among male handball players with respect to different playing position. I have selected thirty two (32) male handball players from Department of Physical Education and Sports Sciences, Annamalai university, Chidambram, Tamilnadu, India. These players were classified into four groups as backs (n = 12), wings (n = 7), pivots (n = 7) and goalkeepers (n = 6) respectively. These selected subjects, who practice handball regularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the present study small-sided handball game training for eight weeks significantly decreased total sprint time and fatigue index by 4.19% and 34.9% respectively. Earlier Chittibabu (12) found a significant correlation between maximal oxygen consumption and fatigue index of male handball players. It states that handball players with greater maximal oxygen consumption had lower fatigue index.…”
Section: Total Sprint Time and Fatigue Indexmentioning
confidence: 89%
“…In the present study small-sided handball game training for eight weeks significantly decreased total sprint time and fatigue index by 4.19% and 34.9% respectively. Earlier Chittibabu (12) found a significant correlation between maximal oxygen consumption and fatigue index of male handball players. It states that handball players with greater maximal oxygen consumption had lower fatigue index.…”
Section: Total Sprint Time and Fatigue Indexmentioning
confidence: 89%
“…Different sports events demand a combination of different physical variables for high quality performance. Several studies showed a significant relationship between speed and agility in handball players [8][9][10][11]. Accordingly, the ability to accelerate, defined as the rate of change in velocity, is more important to successful performance than maximum velocity [12].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that playing ability has significant relationship with fitness parameters. scholars stressed that more time should be dedicated to sprint training and leg muscle strength and power training, in order to increase sprint performance [14,15,7]. During a handball match the players has to sprint for fast break, defense and offence and similarly they perform feints, change of directions.…”
Section: Discussionmentioning
confidence: 99%